Advanced exergy analysis on varying climate conditions for a 3 MW S-CO2 Brayton cycle system - Zhen Wang; Decai Zhao; Bo Wang; Xiang Xu (Case Studies in Thermal Engineering)
Aiming at the problem that conventional exergy analysis cannot provide comprehensive insights into exergy destruction, advanced exergy analysis was conducted on the supercritical CO2 cycle. A more detailed breakdown of exergy destruction was revealed. In addition, the effects of ambient temperature on various exergy destruction under off-design conditions were innovatively discussed. The system's exergy analysis results show that the thermal and exergy efficiency under rated conditions are 33.29 % and 46.06 %, respectively. The system's avoidable exergy destruction is 0.95 MW (34.87 % of the total exergy destruction). This avoidable exergy destruction comprises 52.69 % endogenous and 47.31 % exogenous contributions. Within the compressor inlet temperature range of 303.15 K–308.15 K, the regenerator's avoidable exergy destruction accounts for a consistently high proportion of the total and increases with the ambient temperature. The system's endogenous exergy destruction exhibits a downward trend, indicating that greater attention should be directed to interactions between components as the ambient temperature rises. The avoidable portion of the total system exergy destruction ranges from 30.99 % to 53 %, suggesting significant potential for optimization. The advanced exergy analysis conducted in this study will guide the improvement of the system and determine the direction of component improvement by considering ambient temperature effects.